Comparison of anteroposterior lip positions of the most preferred facial profiles of the Nepalese people - Bajracharya, Manish; Parajuli, Umesh; Khanal, Abhilasha; Shrestha, Neesha; Pyakurel, Ujjwal (Orthodontic Journal of Nepal, 2021)
Introduction: Though cephalometric analysis of both hard and soft tissue has been done extensively for the treatment planning in orthodontics and orthognathic surgery in Nepalese people for years, they are all based on the norms for the Caucasians. No research has been done to establish the most favored profile amongst the Nepalese. The purpose of this study was to find out the most preferred well balanced or most favored facial profile from a series of 13 silhouettes with varying position of anteroposterior lip position by a group of Nepalese lay persons and general dental surgeons. Materials and Methods: Average profile for male and female were constructed from the profile of 50 Nepalese males and females with normal occlusions and without history of orthodontic and prosthetic replacement. The lips were then protruded or retruded in 1-mm increments and a series of 13 silhouettes were constructed for each male and female with the average profile in the center. The silhouettes were then given to 500 dental surgeons and lay persons each and were asked to rank the 3 most preferred facial profiles in order of preferences. Result: Both the general dental surgeons and the lay persons tend to prefer flatter profile than average for both the sexes. Both the groups preferred more flat profile for women compared to males. The least favored profile was the most protrusive one for both the groups. Conclusion: This research shows that lay persons and the general dental surgeons preferred retruded profile than the average profile though prior research show that Nepalese people have an average profile convex